2018
DOI: 10.1098/rsos.181667
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and visible–near-infrared luminescence of Bi-doped gehlenite glass

Abstract: Gehlenite glass microspheres, doped with a different concentration of Bi3+ ions (0.5, 1, 3 mol%), were prepared by a combination of solid-state reaction followed by flame synthesis. The prepared glass microspheres were characterized from the point of view of surface morphology, phase composition, thermal and photoluminescence (PL) properties by optical and scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC) and PL spectroscopy. The closer inspection of glass mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Aluminum MAS NMR experiments were performed on a 500 MHz Bruker AVANCE III spectrometer operating at 130.32 MHz for 27 Al, and equipped with a double resonance 4 mm probe head. X-ray photoelectron spectroscopy (XPS) measurements were carried out on an AXIS Supra electron spectrometer (Kratos Analyical Ltd.) with base vacuum in the analysis chamber in the order of 10 -8 Pa.…”
Section: Preparation Of Ag@zx-bimentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum MAS NMR experiments were performed on a 500 MHz Bruker AVANCE III spectrometer operating at 130.32 MHz for 27 Al, and equipped with a double resonance 4 mm probe head. X-ray photoelectron spectroscopy (XPS) measurements were carried out on an AXIS Supra electron spectrometer (Kratos Analyical Ltd.) with base vacuum in the analysis chamber in the order of 10 -8 Pa.…”
Section: Preparation Of Ag@zx-bimentioning
confidence: 99%
“…The unexpected detection of Bi 2+ in ZX-Bi-3 sample reveals a chemical reduction of Bi 3+ precursor during the synthesis process. The reduction of Bi 3+ to its lower-valence bismuth ions usually occurs after thermal treatment at a relatively high temperature under anaerobic atmosphere conditions 27 . The low synthesis temperature (50°C) excludes the thermal reduction hypothesis, which is probably due to the in in-situ loading of Bi in presence of metallic alumina in the synthesis, characterized with a very low standard potential (-1.67 V SHE, for Al 3+ /Al at 25°C) in respect to Bi 3+ /Bi (+0.317V SHE at 25°C).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…The precursor powder with gehlenite composition (50 mol% calcium oxide, 25 mol% aluminium oxide and 25 mol% silicon dioxide) was prepared by solid-state reaction, from high-purity chemicals (SiO 2 ; p.a., Polske odczynniki chemiczne, Gliwice; Al 2 O 3 ; p.a., Centralchem, Bratislava; CaCO 3 (p.a., Centralchem, Bratislava). The details are described in our previous work [9]. From precursor powder, the glass microspheres were prepared by flame synthesis [41,42].…”
Section: Preparation Of Glass Microspheresmentioning
confidence: 99%
“…They found that the photoluminescent properties of Eu 2+ are influenced by the crystal structure of Ca 2 Al 2 SiO 7 , and gehlenite thus has the potential to become a single component luminophore emitting warm white light in the production of white LEDs. Gehlenite doped with Bi 3+ exhibits PL emissions in different spectral regions (visible, deep red and NIR range) indicating the presence of Bi in various oxidation states (Bi 3+ , Bi 2+ and Bi + ) [9].…”
Section: Introductionmentioning
confidence: 99%